A widow's vengeance after the wars of religion. Gender and justice in renaissance France. By Tom Hamilton. Pp. xxvi + 212 incl. 19 ills and 1 map. Oxford-New York: Oxford University Press, 2024. £76. 978 0 19 287017 9 - Barker, Sara (The journal of ecclesiastical history, 2025)
A widow's vengeance after the wars of religion. Gender and justice in renaissance France. By Tom Hamilton. Pp. xxvi + 212 incl. 19 ills and 1 map. Oxford-New York: Oxford University Press, 2024. £76. 978 0 19 287017 9 - Volume 76 Issue 3